Implementation of Principal’s Leadership in Improving Teacher Performance - Suyipto, Edi; Ahyani, Nur; Fitria, Happy (Yayasan Sembilan Pemuda Indonesia, 2023)
This is descriptive qualitative research using interview data collection techniques and field observations. This study aims to look at the principal’s leadership in increasing teacher performance at SD Negeri 10 Koba, Central Bangka Regency. Teacher performance can be reviewed and measured based on the content that must be owned by every educator. It can be displayed through the dominance of pedagogic, professional, personality and social competencies. Considering that the principal’s leadership on teacher performance is very influential, it is suggested that at SD Negeri 10 Koba, Central Bangka Regency, increasing teacher performance can be done through career development for teachers through training or educational seminars.